Body Mass Index in adults aged 20-75 years related to Metabolic Parameter in Marginal Posbindu PTM Area DKI Jakarta: Body Mass Index in adults aged 20-75 years related to Metabolic Parameter in Marginal Posbindu AREA PTM Area DKI Jakarta - Puspita Sari, Bela; Narliani, Eka Rowiyan; Mulyani, Erry Yudhya (Alta Dharma Publisher, 2022)
Background: Obesity or high body mass index is one of the factors that is associated with metabolic parameters. Metabolic parameter that include blood sugar, blood lipid , blood pressure and uric acid are the important factor for serious degenerative diseases. The data of metabolic parameters in marginal area in North Jakarta is limited. Understanding the relationship of body mass index and metabolic parameters is warranted.. Objective The study aimed to examine the relationship between body mass index and metabolic parameter in marginal area of North Jakarta. Methods: A cross-sectional study was applied in this study. The data was carried out from secondary data from the North Jakarta LKC Dompet Dhuafa Research. A total of 657 samples age 20-75 were selected using random cluster sampling. Results: The results found that there is a significant relationship between BMI and blood glucose (p-value ? 0.05) and a ratio value of 0.445 at the age of 20- 30. A significant relationship exists between BMI and blood glucose (p-value of 0,027 ) and a ratio value of – 0.111 at 50-75 years old. There is no significant relationship of body mass index with other metabolic parameter such as blood pressure, blood lipid and uric acid in different age range. Conclusion: Blood glucose may have relationship with body mass index among young adults